Trädgårdsängen: nature close at hand - Delin, Jonas (My University, 2022)
More people move from larger cities to other municipalities than ever before. The net emigration from Stockholm 2020 was 4618 individuals compared to 2019 where the netimmigration was 4870 individuals. This is also the trend in Gothenburg where the total loss of population was 2382 in 2020. There is a preponderance in these numbers of families with children and most move to smaller municipalities close to their original cities. The reasons are problems in the housing market as well as a rise in environmental interests such as closeness to nature, the possibility to cultivate crops and to provide a healthy environment for children to grow up in. This does not only affect the larger municipalities as an excessive loss of tax income but also leads to an ageing population in cities. Farmable land is also destroyed in the process of creating dwelling in smaller municipalities and farmers all over Sweden are pulling the breaks on developing land for housing. If the same kind of typology could be found in the same municipality as cities, this loss of tax and destruction of farmland could be avoided, as well as keeping the younger adult population. This project circles around how one could design affordable single-family housing of the villa-typology within, or in the suburbs of, a city. The project incorporates proximity to nature as well as gradients of private outdoor space in an urban setting. Accessibility of and within the community is of great importance as well as a sense of privacy between residents. The cost of the production is kept low using pre-fabricated modules of light wooden construction, including furnished kitchen, toilets and fixed furnishings. This significantly decreases work-time on site as well as opening the possibility of creating quality houses in bulk. The chosen site, Angered, has nature close at hand and here it is close to both swimming, fishing, mushroom picking and outdoor life in the nature reserve Vättlefjäll with its untouched nature.
Keywords: Housing, pre-fabrication, wooden construction